Green Tax As A Solution To Reduce The Use Of Plastic Bags In The Retail Industry In Indonesia - Rizka, Nor Rahma; Sajidah, Hana; Azizah, Noor Aulya; Ramadhani, Octavia (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
The presence of plastic waste in Indonesia has become increasingly alarming. Indonesia is the second-largest contributor to plastic waste globally, after China. Plastic waste falls into the category of non-biodegradable waste, requiring a long time to decompose, making it highly hazardous to the environment. Plastic products, such as plastic bags from retail business activities and the lack of public awareness regarding their use, are among the largest contributors to plastic waste in Indonesia. The main objective of this study is to examine the effectiveness of Green Tax policies implemented in other countries' retail industries as a means of reducing plastic bag usage, formulate the Green Tax concept as a solution for reducing plastic bag usage in Indonesia’s retail industry, and identify the challenges and benefits it brings to the country. The research method used in this study is a literature review by analyzing articles and scholarly journals from data-based sources such as Google Scholar regarding Green Tax in efforts to reduce plastic bag usage. The results of the literature review indicate that the Green Tax concept can be implemented in Indonesia’s retail industry through a plastic bag tax, where each plastic bag used will be subject to an additional charge, with part of the revenue allocated to environmental conservation. Beyond shifting the burden onto consumers in the retail industry, the Green Tax concept also serves as a solution for reducing plastic bag usage by encouraging environmentally friendly behavior and fostering a sustainable circular economy initiative. The success of the Green Tax concept relies heavily on the crucial roles of all stakeholders, including the government, retail companies, the Indonesian Olefin and Plastic Industry Association (INAPLAS), environmental conservation organizations, and the public.